2022
DOI: 10.3390/ma15145075
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Physicochemical, Mechanical, and Photocatalytic Antibacterial Properties of a Methacrylate-Based Dental Material Loaded with ZnO Nanoparticles

Abstract: While resin-based materials meet the many requirements of a restorative material, they lack adequate, long-lasting antimicrobial power. This study investigated a zinc oxide nanoparticle (ZnO NP)-loaded resin-blend (RB) toward a new antimicrobial photodynamic therapy (aPDT)-based approach for managing dental caries. The results confirmed that up to 20 wt% ZnO NPs could be added without compromising the degree of conversion (DC) of the original blend. The DC achieved for the 20 wt% ZnO NP blend has been the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 75 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Shi et al demonstrated that periodontal ligament stem cells labeled with superparamagnetic iron oxide NPs could induce changes in the oral microbiota, assisting in periodontal bone regeneration, suppressing inflammation, and achieving antibacterial effects simultaneously [ 48 ]. Comeau et al highlighted that resin composite materials loaded with zinc oxide NPs exhibited excellent antibacterial properties, providing a novel approach for dental caries management based on antibacterial photodynamic therapy [ 49 ]. Additionally, an in vitro study has revealed that the combination of minocycline and cobalt oxide NPs can endow pits and fissure sealants with formidable antibacterial potential, thereby mitigating the occurrence of complications such as microleakage and secondary caries [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al demonstrated that periodontal ligament stem cells labeled with superparamagnetic iron oxide NPs could induce changes in the oral microbiota, assisting in periodontal bone regeneration, suppressing inflammation, and achieving antibacterial effects simultaneously [ 48 ]. Comeau et al highlighted that resin composite materials loaded with zinc oxide NPs exhibited excellent antibacterial properties, providing a novel approach for dental caries management based on antibacterial photodynamic therapy [ 49 ]. Additionally, an in vitro study has revealed that the combination of minocycline and cobalt oxide NPs can endow pits and fissure sealants with formidable antibacterial potential, thereby mitigating the occurrence of complications such as microleakage and secondary caries [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Materials frontiersin.org 10 based restorative materials loaded with ZnO NPs have promising applications in dentistry (Comeau et al, 2022). This structure can also influence the properties of nanomaterial-based PSs.…”
Section: Figurementioning
confidence: 99%